trans-Diaquabis[5-carboxy-2-(3-pyridyl)-1H-imidazole-4-carboxylato-κ(2) N (3),O (4)]manganese(II) - Chen, Li-Zhuang (International Union of Crystallography, 2008)
In the title compound, [Mn(C(10)H(6)N(3)O(4))(2)(H(2)O)(2)], synthesized by hydrothermal reaction, the Mn(II) ion lies on an inversion centre and displays a distorted octahedral coordination geometry defined by the two imidazole N atoms and two carboxylate O atoms of the two trans-standing chelate ligands, and two O atoms of the water molecules. A two-dimensional supramolecular architecture is formed via N—H⋯O, O—H⋯N and O—H⋯O hydrogen-bonding interactions.